Exploring Offer Speech Acts (Moushide) in Japanese Family Contexts: A Case Study from Kimono Mom’s YouTube Channel - Nurjaleka, Lisda; Haniawati, Nur Abida; Supriatnaningsih, Rina (DBSMB, Vocational College of Universitas Gadjah Mada, 2025)
This study examines the speech act of offering (moushide) and its responses in the context of Japanese family interactions, as featured on the YouTube Channel “Kimono Mom”. Employing a descriptive qualitative approach, this study analyzes conversations from 37 videos containing offer-related speech acts. Data were collected using the “listen-and-note-taking method” and analyzed based on Yoshinari’s (2008) theory of moushide. The findings reveal 40 instances of offer speech acts and 37 responses, classified into six types of offer speech acts-such as direct offers (tenteiteki) and indirect forms like action-based offers (chokusetsu koudou)-and five types of responses, including verbal acceptance and non-verbal gestures. This study highlights the nuanced dynamics of offering within family interactions, emphasizing the interplay of language and context in Japanese pragmatics. By investigating natural and spontaneous discourse, this study contributes to a deeper understanding of interpersonal communication in Japanese, offering practical insights for language learners.